2016
DOI: 10.1049/el.2015.3218
|View full text |Cite
|
Sign up to set email alerts
|

Curvelets‐based ECG steganography for data security

Abstract: Biomedical signals transmitted over the internet are usually tagged with patient information. Data hiding techniques such as steganography ensures the security of such data by hiding the data into signals. However, data hiding results in signal deterioration that might affect diagnosability. A novel technique which uses curvelet transforms to hide patient information into their ECG signal is presented. Curvelet transform decomposes the ECG signal into frequency sub-bands. A quantisation approach is used to emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 9 publications
0
26
0
1
Order By: Relevance
“…By considering the ECG signal distortion due to the addition of watermark bit (i.e., patient's detail), a Curveletsbased method is proposed by Jero et al in [10]. In [10], a Curvelet transform is used to decompose the ECG signal into frequency sub-bands. Then, in the high frequency subbands, watermark bits are embedded using QIM.…”
Section: A Data Hiding Methods Developed For Ecg Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…By considering the ECG signal distortion due to the addition of watermark bit (i.e., patient's detail), a Curveletsbased method is proposed by Jero et al in [10]. In [10], a Curvelet transform is used to decompose the ECG signal into frequency sub-bands. Then, in the high frequency subbands, watermark bits are embedded using QIM.…”
Section: A Data Hiding Methods Developed For Ecg Signalsmentioning
confidence: 99%
“…Using the position information and the threshold selection algorithm, watermark bits are extracted. The method in [10] can disturb certain important parts of an ECG signal. The method in [10], alters the signal even in the medically significant region and therefore limiting the usability in practice.…”
Section: A Data Hiding Methods Developed For Ecg Signalsmentioning
confidence: 99%
“…Recently, Jero and Ramu studied the watermarking of arrhythmic ECG signal [ 22 ] and proposed replacing regular wavelets by curvelets-based transform to hide valuable patient information into the ECG signal [ 23 , 24 ]. Their paper also proposed an adaptive selection of the watermarks location, however without relation to the ECG medical content.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, data hiding has played a crucial role in protecting secret data in multimedia files, such as documents, images, and videos [1][2][3][4][5]. In addition, several researchers have presented data hiding for biomedical signals such as an electrocardiogram (ECG) to secure personal sensitive information, including patients' diagnoses [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, their proposed method provided a payload size of 4,489 bits. By using curvet transform and quantization techniques, Jero and Ramu [10] developed a simple ECG steganography for data security. Simulations indicated that the percentage residual difference (PRD) and BER of the method were 0.110 and 31.84%, respectively; the size of the payload was 4,016 bits.…”
Section: Introductionmentioning
confidence: 99%